Citizen science and roadkills: trends along project lifespan and comparison of tropical and temperate projects (UNED Research Journal, 2018)
The collection of scientific data by people without a science degree is at least as old as Antonie van Leeuwenhoek, but thanks to smartphones it now involves large numbers of volunteers, leading to studies about who the so called “citizen scientists” are, how they behave, and how to improve their work. There are, however, no worldwide studies about citizen science projects reporting fauna killed in road collisions. Here we analyze data from the 31 projects available in September 2017 in iNaturalist.org, the largest website for this subject. The USA and Europe have the most projects, but after correcting for population size, countries like Costa Rica and Canada are outstanding, possibly thanks to widespread Internet access and high educational levels. Projects had a mean of 431 observations, 48 species, of 32 volunteers who, on average, posted 19 observations each. Most volunteers contributed few records and were active only briefly. The roadkill data shows that, in the tropics, seasonal mortality trends match the movement of animals in search of water for drinking and for reproduction, while in temperate sites project differences depended mostly on which particular species is studied. We recommend future consideration of how the behavior of volunteers and projects changes along time, a subject that has seldom been considered in previous studies
Keywords: road mortality; road ecology; community; volunteers; online database